The effect of Augmented Reality (AR) to enhance learning motivation, cognitive intelligence, and self-efficacy in Physical Education - Rifqi Festiawan; Eko Sumanto; Jose Vicente Garcia Jimenez; Arisman Arisman; Taufik Rahman; Danang Endarto Putro; Syahrir Syahrir; Eko Prabowo; Muchtar Hendra Hasibuan; Catur Wahyu Priyanto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Technological innovation in education, particularly Augmented Reality (AR), presents new opportunities to enhance motivation, cognitive abilities, and self-efficacy in physical education.